2019
DOI: 10.1111/are.14413
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of bronopol in grass carp, Ctenopharyngodon Idella , at 15 and 20°C

Abstract: This study explored the pharmacokinetic characteristics of bronopol in grass carp (Ctenopharyngodon idella) under different temperatures. The concentrations of bronopol in the plasma and tissues (kidney, liver and muscle) of grass carp after soaking in bronopol (6.75 µg/ml) at 15 and 20°C were determined using liquid chromatography–mass spectrometry. The concentrations of bronopol in both plasma and tissue first increased and then decreased with soaking time at both tested temperatures. The peak bronopol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The plasma pharmacokinetics of enrofloxacin has been reported in some fish species, such as crucian carp (11,12), large yellow croaker (13), tilapia (14), snakehead fish (15), brown turbot (16), and salmonids (17). In addition to those pharmacokinetics studies, the tissue distribution of enrofloxacin has also been reported in aquaculture species, including northern snakeheads (18), rainbow trout (19,20), grass carp (21), largemouth bass (22), and pacu (23). Those previous results indicated that the plasma and tissues kinetics of enrofloxacin might be strongly influenced by fish species, body conditions, routes of administration, water temperature, and other environmental factors.…”
Section: Introductionmentioning
confidence: 96%
“…The plasma pharmacokinetics of enrofloxacin has been reported in some fish species, such as crucian carp (11,12), large yellow croaker (13), tilapia (14), snakehead fish (15), brown turbot (16), and salmonids (17). In addition to those pharmacokinetics studies, the tissue distribution of enrofloxacin has also been reported in aquaculture species, including northern snakeheads (18), rainbow trout (19,20), grass carp (21), largemouth bass (22), and pacu (23). Those previous results indicated that the plasma and tissues kinetics of enrofloxacin might be strongly influenced by fish species, body conditions, routes of administration, water temperature, and other environmental factors.…”
Section: Introductionmentioning
confidence: 96%
“…6 To protect food health and safety, the detection of FFC residue in animal and meat-derived foods has been gradually emphasized. [7][8][9][10][11][12][13][14] Chloramphenicol analogs usually have low residue levels in aquatic products, thus, it is necessary to use high sensitivity and low detection limit assays to detect them.…”
Section: Introductionmentioning
confidence: 99%